2018
DOI: 10.1002/ece3.4378
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and temporal variations in floral scent in the subdioecious shrub Eurya japonica Thunb

Abstract: In many flowering plants, floral scents are a significant trait for visitors, playing an important role in attracting pollinators and/or detracting herbivores. The evolution of flowering plants from hermaphroditism to dioecy is often accompanied by sexual dimorphism in floral scent. In this study, floral scents emitted by different sexual morphs of the subdioecious shrub Eurya japonica Thunb. were collected using a dynamic headspace method, and sexual and temporal variations were evaluated by gas chromatograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
(77 reference statements)
1
5
0
Order By: Relevance
“…Sexual differentiation of floral scent might be expected in genus Eurya , as this difference has been observed both in E. japonica [ 22 , 23 ] and in this study. Miyazawa et al, reported the different compositions of essential oils of male and female flower buds in E. japonica [ 23 ], and Wang et al, compared the flower scent of E. japonica using a dynamic headspace method [ 22 ]. The same species was examined in these two studies; however, different sampling types lead to different results.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Sexual differentiation of floral scent might be expected in genus Eurya , as this difference has been observed both in E. japonica [ 22 , 23 ] and in this study. Miyazawa et al, reported the different compositions of essential oils of male and female flower buds in E. japonica [ 23 ], and Wang et al, compared the flower scent of E. japonica using a dynamic headspace method [ 22 ]. The same species was examined in these two studies; however, different sampling types lead to different results.…”
Section: Discussionsupporting
confidence: 60%
“…So far, most of the studies addressing Eurya plants have concentrated on morphology and anatomy; only a few studies have focused on floral scent components. Wang et al, reported two components of E. japonica : α-pinene and linalool [ 22 ]. Motooka et al, detected 87 compounds in essential oils from E. japonica flowers, and the main compounds were linalool, (9Z)-tricosene, and nonanal [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Solanaceae linalool and its enantiomers [26] Eurya japonica Thunb Theaceae α-pinene, linalool [27] Gardenia jasminoides Rubiaceae farnesene, Z-3-hexenyl tiglate, indole [28] Gelsemium sempervirens (L.) J. St.-Hil. Gelsemiaceae (Z)-α-ocimene, α-farnesene [29] Gossypium hirsutum Malvaceae (3S)-linalool GhTPS12 [30,31] Jasminum spp.…”
Section: Datura Wrightiimentioning
confidence: 99%